2017
DOI: 10.1007/s10753-017-0712-4
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid Inhibits the IL-1β-Induced Inflammation via MAPK Downregulation in Rat Chondrocytes

Abstract: Osteoarthritis (OA) is a degenerative joint disease frequently seen in the elderly population. Sinapic acid (SA), a commonly found phenolic acid, has been pharmacologically evaluated for its anti-inflammation effects in various studies. To explore its potential therapeutic role for OA, rat chondrocytes were treated with IL-1β (10 ng/ml) with different concentrations of SA in vitro. Our study revealed that SA could inhibit the IL-1β-induced production of nitric oxide (NO) and prostaglandin E2 (PGE2). Consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Cox-2 mainly exists in the nuclear membrane and is not expressed in resting state only when chondrocytes were stimulated by IL-1b and other substances. Previous studies have found that controlling the expression of Cox-2 could suppress the inflammation in the early stage of OA, so as to alleviate symptoms and relieve pain [21]. We also found that IL-1b induced overexpression of Cox-2 and the combination with LBP suppressed the level of Cox-2.…”
Section: Discussionsupporting
confidence: 61%
“…Cox-2 mainly exists in the nuclear membrane and is not expressed in resting state only when chondrocytes were stimulated by IL-1b and other substances. Previous studies have found that controlling the expression of Cox-2 could suppress the inflammation in the early stage of OA, so as to alleviate symptoms and relieve pain [21]. We also found that IL-1b induced overexpression of Cox-2 and the combination with LBP suppressed the level of Cox-2.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, the IL‐1β‐induced downregulation of Collagen II could be ameliorated by BBR. This result is consistent with previous studies (Huang et al, ). Moreover, MAPK signaling was evaluated to clarify the anti‐catabolic and anti‐inflammatory mechanisms; the results showed that BBR can suppress the ability to decrease the production of inflammation‐associated proteins through the MAPK signal pathway.…”
Section: Discussionsupporting
confidence: 94%
“…However, it seems that sinapic acid does not act on the same pathway in all cells. In human hair follicle dermal papilla cells, sinapic acid induces AKT activation and promotes hair growth [32], whereas in rat chondrocytes, sinapic acid inhibits IL-1β induced MAPK, thereby reducing inflammation [33]. ese data indicate that the mechanism of sinapic acid varies from cell to cell.…”
Section: Discussionmentioning
confidence: 98%